2020
DOI: 10.3399/bjgpopen20x101001
|View full text |Cite
|
Sign up to set email alerts
|

Patient symptom experience prior to a diagnosis of oesophageal or gastric cancer: a multi-methods study

Abstract: BackgroundLate stage diagnosis of oesophageal and gastric cancer is common, which limits treatment options and contributes to poor survival.AimTo explore patients' understanding, experience and presentation of symptoms before a diagnosis of oesophageal or gastric cancer.Design & settingBetween May 2016 and October 2017, all patients newly diagnosed with oesophageal or gastric cancer were identified at weekly multidisciplinary team meetings at two large hospitals in England. A total of 321 patients were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 38 publications
3
23
0
2
Order By: Relevance
“…In this study, experiences of survival with EC were designated as problems associated with food intakes, treatment side effects, reduced quality of life, psychological and physical impairments. The nding is in line with studies that recounted experiences of severe malnutrition, a sense of despair, and lack of psychological support among cancer patients (1,2). Studies have shown that the local effect of the tumor itself, host response, hypermetabolism, impaired organ function, therapy-related symptoms, and radiation enteritis results in a high prevalence of malnutrition among patients who undergo palliative cancer care (31)(32)(33).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, experiences of survival with EC were designated as problems associated with food intakes, treatment side effects, reduced quality of life, psychological and physical impairments. The nding is in line with studies that recounted experiences of severe malnutrition, a sense of despair, and lack of psychological support among cancer patients (1,2). Studies have shown that the local effect of the tumor itself, host response, hypermetabolism, impaired organ function, therapy-related symptoms, and radiation enteritis results in a high prevalence of malnutrition among patients who undergo palliative cancer care (31)(32)(33).…”
Section: Discussionsupporting
confidence: 82%
“…In this study, EC patients experienced various vague gastrointestinal disturbances and advanced symptoms characterized by dysphagia and weight loss but none of the early GI disturbances were considered as the symptoms that are associated with esophageal cancer. A previous study demonstrated the experience of imprecise early symptoms among EC patients (1). Failure to associate the minor symptoms with E C maybe because of the similarities of such symptoms to non-cancer conditions at the early stages of the illness (21).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, except for dysphagia, none of the GI disturbances were considered as the symptoms that are associated with esophageal cancer. A previous study demonstrated the experience of imprecise early symptoms among EC patients (1). Failure to associate the minor symptoms with E C maybe because of the similarities of such symptoms to non-cancer conditions at the early stages of the illness (24).…”
Section: Discussionmentioning
confidence: 97%
“…Gastric cancer remains one of the most common malignancies all over the world, particularly in Asia 1 - 3 . Most patients are diagnosed with advanced stages on account of unspecific symptoms 4 , 5 . There are still no curable treatments but only approved treatments like chemotherapy and immunotherapy for metastatic gastric cancer patients currently 6 .…”
Section: Introductionmentioning
confidence: 99%